One year outcome and analysis of peri-device leak of left atrial appendage occlusion devices. (14th October 2021) - Mansour, M; Harnay, E; Al Ayouby, A; Mansourati, V; Jobic, Y; Gilard, M; Le Ven, F; Mansourati, J
Abstract: Background: The prevalence of peri-device leak (PDL) of left atrial appendage occlusion (LAAO) devices has been previously reported. However, there have been only few data that compared different existing devices. The aim of this study was to assess the incidence of PDL with both devices WATCHMAN® and AMPLAZER Amulet®, and to evaluate the clinical outcome at 12 months. Methods: Consecutive patients who underwent LAAO between January 2018 and 2020 were randomly assigned to either WATCHMAN or AMPLATZER Amulet implantation based on a systematic two-week alternation between both devices. LAA measurements were assessed using cardiac computed tomography angiography (CCTA) prior to, and transesophageal echocardiography (TEE) during the procedure. At 8 weeks post-LAAO, patients underwent TEE and/or CCTA to identify the presence of PDL and/or device-related complications. Patients were then followed for 12 months to identify major adverse cardiovascular/embolic events. Results: The cohort consisted of 51 patients (25 WATCHMAN, 26 AMPLATZER Amulet; mean age 76±7 years; male gender 76%). Both groups were identically matched for demographics, comorbidities and indication for LAAO. There were 19 patients who had PDL (13 WATCHMAN vs 6 AMPLATZER Amulet, P-value=0.033). Of them, 8 (15%) patients had significant PDL (7 WATCHMAN vs. 1 AMPLATZER Amulet, P-value=0.018). On CCTA, the landing zone maximal diameter of the AMPLATZER Amulet device had the strongest correlation with the final deployed device size (Spearman'rho 0.92, P-value<0.0001). In the multivariate analysis, male gender and device type were independent predictors of any PDL (P-values 0.016 and 0.031, respectively). On a mean follow-up of 12 months, the total number of events was more prevalent in the WATCHMAN group (P-value 0.008), but the incidence of cardio-embolic events reached borderline significance (16% vs. 0%, P-value=0.051). Conclusions: Among patients who underwent LAAO, almost 15% had significant PDL with the majority belonging to the WATCHMAN group. Still, larger studies are warranted to evaluate its effectiveness in stroke prevention. Funding Acknowledgement: Type of funding sources: None.